The "Dual‐Pathway" Strategy after Acute Coronary Syndrome: Rivaroxaban and Antiplatelet Agents in the ATLAS ACS 2‐TIMI 51 Trial. Issue 5 (October 2014) - Cohen, Marc; Iyer, Deepa
Summary Acute coronary syndrome (ACS) is a medical emergency often associated with an occlusive coronary event with consequent myocardial underperfusion. Patients require immediate antiplatelet therapy and long‐term antithrombotic prophylaxis to reduce the risk of recurrence. Acetylsalicylic acid (ASA) alone or in combination with a platelet P2Y12 inhibitor (dual antiplatelet therapy [DAPT]) has become the clinically accepted antithrombotic prophylaxis for patients post‐ACS. Historically, studies assessing the utility of adding oral anticoagulants (OACs) have not demonstrated a clinical benefit with regard to acceptable bleeding risk. Studies with vitamin K antagonists (VKAs) such as warfarin demonstrated a potential to reduce the risk of subsequent death by reinfarction but this benefit was offset by increases in bleeding. Results from studies of two targeted non‐VKA OACs also proved disappointing, with little or no apparent reduction in the rate of ischemic events seen. However, the recent ATLAS studies assessing rivaroxaban (an oral factor Xa inhibitor) in patients with ACS demonstrated a reduction in the composite endpoint of deaths from cardiovascular causes, myocardial infarction (MI), or stroke, and a reduction in the rate of stent thrombosis. This review provides an overview of the pivotal studies in which the addition of OACs to antiplatelet therapy (the so‐called "dual‐pathway" approach) has been investigated for the management of patients post‐ACS and considers the results of the ATLAS studies and their potential impact on the management of patients after an acute event.